Chloroplast-like porous bismuth-based core–shell structure for high energy efficiency CO2 electroreduction - Wang, Yi-Rong; Yang, Ru-Xin; Chen, Yifa; Gao, Guang-Kuo; Wang, Yu-Jie; Li, Shun-Li; Lan, Ya-Qian (Science bulletin (Beijing), 2020)
[Display omitted] Electrochemical CO2 reduction reaction (CO2RR) to formate is economically viable considering the energy input and market value. Through learning nature, a series of chloroplast-like porous bismuth-based core–shell (CPBC) materials have been designed. In these materials, the porous carbon can enrich and transfer CO2 to the core–shell Bi@Bi2O3 in CO2 reduction process, during which Bi2O3 layer can be transformed into activated metastable layer to efficiently convert CO2 into formate and Bi can provide abundant electrons. Based on this, superior performances for most of important parameters in CO2RR can be achieved and best of them, CPBC-1 presents remarkable Faradaic efficiency (FEformate > 94%) over a wide potential range (−0.65 to −1.0 V) with high catalysis durability (>72 h). Noteworthy, its maximum energy efficiency is as high as 76.7% at −0.7 V, the highest one in reported bismuth-based materials. This work opens novel perspectives in designing nature-inspired CO2RR electrocatalysts.